The Implementation of Jurnal Mekari in Enhancing Financial Report Efficiency in The Digital Era at Transformer Center - Fitriyani, Yuniar; Tusmiyani, Tusmiyani (Manajemen Multitalenta Indonesia, 2025)
With the rapid development of digital technology, companies are required to adopt information technology systems to enhance efficiency and effectiveness in financial report management. This study aims to evaluate the impact of implementing the Jurnal Mekari application on improving the efficiency of financial report preparation at Transformer Center in the digital era. Before using this application, financial recording and reporting processes were conducted manually, often resulting in delayed reports, input errors, and lack of transparency in financial information. Through the implementation of Jurnal Mekari software, the company has simplified the recording process, accelerated report preparation, and improved data accuracy in real time. This research employs qualitative methods with a phenomenological approach, using data collection techniques such as in-depth interviews, direct observation, and documentation. The study involved six participants, a head of division, the finance manager and four finance staff members who had been using the application for over three months and was conducted over a three-month period from April to June. The documentation comprised photographic records of the interview outputs. Documentation comprised photographic records of the interview outputs, data were analyzed using thematic analysis.The results show that the implementation of Jurnal Mekari significantly contributes to time efficiency, recording accuracy, financial data transparency, and the productivity of the finance team. Furthermore, this system facilitates management in monitoring processes and making strategic decisions based on up-to-date financial data